EFFECT OF NITRITE ON DENITRIFICATION OF WASTEWATER BY AUTOTROPHIC BACTERIA - Nugroho, Rudi (Center for Environmental Technology, 2006)
Effect of nitrite on denitrification of synthetic wastewater using autotrophic bacteria was evaluated in both batch suspension and continuous packed column runs. Emphasis was placed to clarify the minimum concentrations of nitrite and nitrous acid that inhibit the denitrification rates. Batch suspension runs were conducted by mixing acclimatized denitrification sludge and synthetic wastewater in an Erlenmeyer flask. In continuous runs, denitrification sludge was loaded to a column packed with sulfur and limestone. The nitrite inhibition could be explained satisfactorily by substrate non-competitive inhibition model. The minimum concentration of nitrite which inhibits the nitrate and nitrite removal rate lowered with decreasing pH. In suspension runs, the minimum concentration of nitrous acid which inhibited the nitrite removal rate was 0.043 g-N/m3, while the nitrate removal rates was inhibited below 0.012 g-N/m3.Ã‚Â Both in suspension and continuous packed column runs, nitrate removal was more sensitive against nitrite increase compared with nitrite removal. The minimum concentration of nitrite which inhibited nitrate removal rate in continuous packed column runs was lower than that in suspension runs.Ã‚Â Ã‚Â Keywords:Autotrophic bacteria, denitrification, inhibition, nitrite, sulfurÃ‚Â